REVISITING POVERTY ESTIMATION IN INDIA: INSIGHTS FROM THE NITI AAYOG REPORT AND THE HOUSEHOLD CONSUMER EXPENDITURE SURVEY 2022–23 - Manchanda, Deepak (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Poverty estimation lies at the core of development economics and social policy in India. As a country with a large and diverse population, measuring poverty is not just an academic exercise — it serves as the foundation for designing targeted welfare programs, distributing public resources, and evaluating the effectiveness of policy interventions aimed at inclusive growth. India’s trajectory of poverty reduction has been both complex and contentious, shaped by shifts in methodology, changing consumption patterns, and the interplay between economic growth and inequality.